2014
DOI: 10.4161/15548627.2014.981792
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of autophagy by E3 ubiquitin ligase RNF216 through BECN1 ubiquitination

Abstract: These authors contribute equally to this work.Keywords: autophagy, BECN1, protein degradation, RNF216, ubiquitination Abbreviations: Atg, autophagy-related; BALF, bronchoalveolar lavage fluid; BMDM, bone marrow-derived macrophage; CFU, colony-forming unit; GFP, green fluorescent protein; HRP, horseradish peroxidase; i.t., intratracheally; LPS, lipopolysaccharide; MAP1LC3A, microtubule-associated protein 1 light chain 3 a; MOI, multiplicity of infection; NFKB, nuclear factor of kappa light polypeptide gene enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 62 publications
1
89
0
Order By: Relevance
“…In addition to TRAF6, several other regulatory cofactors, such as BCL-2, DAPK, Cul4, Nedd5, and RNF216, also associate with Beclin-1 to regulate its activity (He and Levine, 2010;Wirawan et al, 2012;Mei et al, 2016). Of these, TRAF6/Cul4 and Nedd4/ RNF216 are two types of E3 ligases that promote the stabilization and degradation, respectively, of Beclin-1 and subsequently regulate autophagy dynamics in mammals (Shi and Kehrl, 2010;Platta et al, 2012;Xia et al, 2013;Xu et al, 2014). Upon induction of autophagy, TRAF6 and Cul4 ubiquitinate Beclin-1 at the K63 residue, which allows it to interact with VPS34 and then activate autophagy (Shi and Kehrl, 2010;Xia et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to TRAF6, several other regulatory cofactors, such as BCL-2, DAPK, Cul4, Nedd5, and RNF216, also associate with Beclin-1 to regulate its activity (He and Levine, 2010;Wirawan et al, 2012;Mei et al, 2016). Of these, TRAF6/Cul4 and Nedd4/ RNF216 are two types of E3 ligases that promote the stabilization and degradation, respectively, of Beclin-1 and subsequently regulate autophagy dynamics in mammals (Shi and Kehrl, 2010;Platta et al, 2012;Xia et al, 2013;Xu et al, 2014). Upon induction of autophagy, TRAF6 and Cul4 ubiquitinate Beclin-1 at the K63 residue, which allows it to interact with VPS34 and then activate autophagy (Shi and Kehrl, 2010;Xia et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…TRAF6 also mediates K63-linked ubiquitination of ULK1, which subsequently promotes the stabilization and self-association of ULK1 and therefore activates autophagy (Nazio et al, 2013). However, recent studies have revealed that K11-and K48-linked ubiquitination of Beclin-1 by the E3 ligases Nedd4 and RNF216, respectively, have an opposite effect from that of K63-linked ubiquitination, instead leading to degradation of Beclin-1 and the suppression of autophagy (Platta et al, 2012;Xu et al, 2014). Although the regulation of autophagosome formation by ubiquitination of ATG proteins has been extensively studied in mammalian cells, it is still unclear whether plant autophagy involves a similar regulatory mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…For example, RNF216 binds to and destabilizes Beclin-1 through K48-linked ubiquitination, whereas USP19 maintains Beclin-1 protein levels through K11-specific deubiquitination. 61,62 Upon induction, xenophagy, reminiscent of other selective autophagic routes, such as mitophagy, utilizes autophagic receptors that bind both a molecular tag attached to the bacterial cargo and the autophagic modifier LC3 to selectively bridge bacterial cargo to the autophagosomal membrane. 63 Ubiquitin appears to represent a common 'eat-me' signal in various selective autophagic pathways including xenophagy.…”
Section: Involvement Of the Ubiquitin System In Antimicrobial Autophagymentioning
confidence: 99%
“…Fluorescence confocal microscopy was performed as previously described (16). Cells grown on coverslips were fixed in BD Cytofix/Cytoperm solution (BD Biosciences) at room temperature for 15 min.…”
Section: Fluorescence Confocal Microscopymentioning
confidence: 99%
“…Cells were directly lysed with RIPA containing protease and phosphatase inhibitors (Roche) and proteins were separated by SDS-PAGE after denaturation (16). Immunoblot analysis was performed by initial transfer of proteins onto polyvinylidenefluoride filters using a Mini Trans-Blot (Bio-Rad) followed by a blocking step with 5% nonfat dried milk plus 0.1% Tween 20 for 2 hours at room temperature and exposed to primary antibodies diluted 2,000-fold that recognized microtubule-associated protein light chain 3 (LC3, Cell Signal), autophagyrelated protein 5 (Atg5, Cell Signal), Rab7 (Cell Signal), or 5000-fold for GAPDH (Santa Cruz) overnight at 4°C and subsequently washed.…”
Section: Immunoblottingmentioning
confidence: 99%